CONCEPTIONS OF TEACHERS FROM THE STATE EDUCATION NETWORK OF SAO PAULO ON SEXUAL EDUCATION - Silva, Erick R. F. de A. [UNESP]; Denari, Fatima E.; Santos, Manoela A. dos (Univ Federal Paraiba, 2017)
Sexual education in school system offers a critical resource for the critical development and political and social emancipation of learners. In this way, the actions implemented in this scope, aimed at promoting a critical awareness about sexuality, should be encouraged and guaranteed by the public power. Thus, the objective of this research is to analyze the conceptions of teachers in the state education network of the State of Sao Paulo on sexual education trying to identify the didactic materials used to implement it. For data collection, interviews were applied and the analysis was based on the theoretical-methodological assumptions of qualitative research. The investigation revealed several educational initiatives aimed at the implementation of sexual education in schools. Teachers showed they are committed to their demands, but they evaluate that classroom practices are still incipient and superficial. The study seeks to explain the dimensions involved in this contradictions and suggests possible solutions.
Keywords: Curriculum; Sexual Education; Sexuality